Statistical Survey for the Physical Characteristic of Near Contact Binary(NCBs) - Kyu-Dong Oh (Journal of Astronomy and Space Sciences, 2005)
The absolute dimensions and orbital elements of 66 near contact binaries, collected from literatures, have been analyzed to investigate the physical characteristics of the near contact binaries as well as co-relations among physical parameters. The relationship between the mass ratio and luminosity ratio of the near contact binary systems have been obtained as a L2/L1 ≈ (M2/M1)^1.45, which is similar to that of the early type contact binary system. The physical parameters of the near contact binaries show that the difference in mass, radius, luminosity and temperature between the primary and the secondary components for the F type NCBs are smaller than those for the A type NCBs. In H-R diagram, the components of the A types are located closer to the terminal age main sequence than those of the F types.